Stress management of undergraduate students at Sisaket Rajabhat University associated with the COVID-19 virus outbreak - Boonrin, Wiraya (UBRU Journal for Public Health Research, 2022)
This study is a cross sectional survey aimed at studying the stress management of undergraduate students at Sisaket Rajabhat University during the COVID-19 pandemic using the undergraduate student stress management questionnaire, Sisaket Rajabhat University. collect data among a sample of 380 students in undergraduate, regular, year 1-4, Sisaket Rajabhat University, academic year 2020, analyze data and present it with frequency, percentage, mean and standard deviation. The results showed that the sample was 72.90 percent female, with mean age of 21 years (S.D. =1.87), the lowest age at 19 years, the highest 24 years, the majority of faculty of education, 36.05 percent in academic performance, mostly academic performance. mean grade (GPA) between 2.51 - 3.00, 46.58 percen has mean monthly income of 2,501 – 3,000 Baht, 36.32 percent of residential characteristics. 62.63 percent of students borrowed from the Education Loan Fund 69.21 percent. Percent overall, students had moderate stress management (Mean=3.38, S.D. =1.18), representing 52 percent When classifying positive stress management statements. It was found that when they feel stressed, students listen to music (Mean=3.94, S.D. =0.91), second only to when they feel stressed, students play Facebook (Mean=3.80, S.D. =1.05) when classifying negative stress management clauses. It was found that when students are very stressed, they are very stressed. Students tend to hurt others (Mean=3.82, S.D. =1.46), second only to feeling stressed. Students smoke (Mean=3.78, S.D. =1.46) Conclusion the results of the study indicate that most students use effective methods of managing positive stress, including listening to music, playing Facebook, but also two-five students have managed negative stress, namely harming others, and smoking, which is a preliminary information for planning to help students managing positive stress by encouraging students to have recreational activities that focus on engaging students, or organizing creative activities through facebook broadcasts, managing negative stress by organizing activities for students to express positive stress by exercising to vent stress and organizing non-smoking campaigns.